2022
DOI: 10.3389/fphar.2022.904314
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 promotes ferroptosis in sorafenib-induced cardiotoxicity by suppressing Slc7a11 expression

Abstract: Sorafenib is the unique recommended molecular-targeted drug for advanced hepatocellular carcinoma, but its clinical use is limited due to cardiotoxicity. As sorafenib is an efficient ferroptosis inducer, the pathogenesis of this compound to ferroptosis-mediated cardiotoxicity is worth further study. Mice were administered 30 mg/kg sorafenib intraperitoneally for 2 weeks to induce cardiac dysfunction and Ferrostatin-1 (Fer-1) was used to reduce ferroptosis of mice with sorafenib-induced cardiotoxicity. Sorafeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Notably, ATF3 plays an important role in regulating ferroptosis, arousing our great attention. For example, Li et al have shown that sorafenib induces ferroptosis-mediated cardiotoxicity in mice ( Li Y. et al, 2022 ). Wang et al have found that quercetin relieves acute kidney injury through inhibiting ATF3-mediated ferroptosis ( Wang Y. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ATF3 plays an important role in regulating ferroptosis, arousing our great attention. For example, Li et al have shown that sorafenib induces ferroptosis-mediated cardiotoxicity in mice ( Li Y. et al, 2022 ). Wang et al have found that quercetin relieves acute kidney injury through inhibiting ATF3-mediated ferroptosis ( Wang Y. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to human tumours and the one investigated human cell line in their study, canine cell lines were more sensitive to sorafenib than vemurafenib 10 . Sorafenib is an important drug for liver cancer therapy in men, primarily through the induction of apoptosis and ferroptosis and it is not a specific BRAF inhibitor, in contrast to vemurafenib 43 . As Jung and colleagues suggest, the different sensitivity of BRAF mutant cancer to sorafenib and vemurafenib in men and dogs may indicate different cancer genetics in men and dogs, innate resistance to vemurafenib in canines, or different drug binding affinity to the BRAF protein in humans and dogs.…”
Section: Discussionmentioning
confidence: 87%
“…So how does sorafenib realize the process of inducing ferroptosis of cardiac cells? Li et al reported that ATF3 promotes ferroptosis in sorafenib-induced cardiotoxicity by suppressing SLC7A11 expression [9]. Jiang et al reported that ATF4 protects against sorafenib-induced cardiotoxicity by suppressing ferroptosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is reported to cause ferroptosis during hepatocellular carcinoma therapy through inhibiting cystine/glutamate antiporter system Xcactivity [8]. Recent studies revealed the critical role of ferroptosis in sorafenib induced cardiotoxicity [9,10].…”
Section: Introductionmentioning
confidence: 99%